Elementy skladowe "czucia przyboru" w opinii zawodniczek i trenerek gimnastyki artystycznej - Starosta, W.; Sanzarowa, N.; Olefir, W.; Pawlowa-Starosta, T. (Sport wyczynowy, 2002)
Introduction. Despite the obvious importance of this phenomenon for movement control in rhythmic gymnastic there is actually no research paying special attention to "apparatus feeling" - its elements, structure, the role in gymnasts' activities. The paper was aimed at (1) an attempt of "apparatus feeling" compete description and its role in gymnasts' activities; (2) an effort to distinguish elements of "apparatus feeling"; (3) determining the manifestation causes of "apparatus feeling". Material and methods. 40 high-class gymnasts and 9 high-class coaches (former gymnasts) took part in the research. The testes were to fill in a questionnaire of 25 "open" questions. The questionnaire asked the testes to describe how they understand "apparatus feeling", the essence of its manifestation, its elements, factors influencing "apparatus feeling", etc. Psychosemantic experiment techniques. Conclusions. The subjective semantic structure of the concept of "apparatus feeling" includes 3 components at least: perception of apparatus physical properties, movement coordination, and mastery techniques. A highly developed "apparatus feeling", on the one hand, requires perfect mastery of the "apparatus techniques", and, on the other hand, this feeling itself is a sign of the gymnast's technical skills.